Two new species of crickets Adelosgryllus Mesa & Zefa, 2004 (Orthoptera, Grylloidea, Phalangopsidae) from the Araripe-Apodi National Forest, State of Ceará, Brazil - Corrêa, Robson Crepes; Pereira, Marcelo Ribeiro; Da Costa, Maria Kátia Matiotti; Szinwelski, Neucir; Martins, Luciano De Pinho; Zefa, Edison (Zootaxa, 2018)
In this paper we describe two new sympatric species of phalangopsid crickets Adelosgryllus from the Araripe-Apodi National Forest, State of Ceará, Brazil, highlighting morphological characters, mainly from male genitalia, tegmina and copulatory papilla. We also present a geographical map for the valid species of the genus, as well as photographs of holotypes and paratypes. The type-material is deposited in the Museu de Zoologia da Universidade de São Paulo (MZUSP).